2020
DOI: 10.1016/j.thromres.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of coagulation indices for direct oral anticoagulant concentration

Abstract: Introduction: Different coagulation indices for direct oral anticoagulants (DOACs) exist in clinical practice, but limited data are available for the diagnostic power of these indices. This review and meta-analysis aims to explore the diagnostic value of coagulation indices for DOACs. Materials and methods: PubMed, Web of Science, EMBASE, Clinical Trials.gov, and the Cochrane Library were searched from inception of each database to 15 February 2020. Studies reporting a relationship between coagulation indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…For example, monitoring may be beneficial in patients with very high or low body mass indexes, or with renal impairment. 41 , 42 Many consider DOACs to be advantageous because regular monitoring is not needed, but for certain patients with nonadherence, monitoring might serve to boost confidence in the effect of DOACs and increase adherence. Patient knowledge about the existence of reversal agents, the frequency of physician communication about these agents, and the influence of knowledge about the agents on adherence requires additional exploration, as does the relationship of these interventions on patient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, monitoring may be beneficial in patients with very high or low body mass indexes, or with renal impairment. 41 , 42 Many consider DOACs to be advantageous because regular monitoring is not needed, but for certain patients with nonadherence, monitoring might serve to boost confidence in the effect of DOACs and increase adherence. Patient knowledge about the existence of reversal agents, the frequency of physician communication about these agents, and the influence of knowledge about the agents on adherence requires additional exploration, as does the relationship of these interventions on patient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pharmacokinetic characteristics, the trough concentration time of dabigatran and rivaroxaban was within 1 hour before the next administration, and the peak concentration time was 3 hours after the next administration. Blood samples were collected according to the above time [9,10] . AXA applied uorescence method, Werfen ACL-TOP-700 instrument, Werfen AXA reagent determination and record.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the aggregate properties were found not to influence the bonding strength when the cohesive failure occurred. Moreover, some studies have shown that asphalt is a selfhealing material, with these properties being directly affected by factors such as temperature [19][20][21]. García explained the 2 Advances in Materials Science and Engineering changes in the self-healing rates of asphalt mixture with temperature using the Arrhenius equation and found that there is a minimum temperature below which asphalt cannot be healed [22].…”
Section: Literature Reviewmentioning
confidence: 99%